Pleistocene to recent scleractinian deep-water corals and coral facies in the Eastern Mediterranean - Taviani, M.; Vertino, A.; López Correa, M.; Savini, A.; De Mol, B.; Remia, A.; Montagna, P.; Angeletti, L.; Zibrowius, H.; Alves, Tiago Marcos; Salomidi, M.; Ritt, B.; et al. (Facies, 2010)
Recent investigations of the Eastern Mediterranean Sea carried out during the GECO cruise with RV Urania provided a substantial number of new cold-water coral (CWC) records, including branching and solitary scleractinian species. These new sites are located along steep escarpments and on topographic highs along the margins of Crete, Karpathos, and Rhodes. The majority of the corals represent fossil occurrences, predominantly Late Pleistocene assemblages. Our research documents that the Eastern Mediterranean Basin has been colonized by CWC at favorable times during the Last Glacial, in particular during the Younger Dryas. Schizocyathus fissilis is reported for the first time for the Mediterranean, while the finding of Ceratotrochus magnaghii represents the first record for the Eastern Mediterranean. Various coral facies occur on the southerly island slopes of Crete, Karpathos, and Rhodes, including hardgrounds and loose skeletal sediments. Hardgrounds occur on steep topographies between ca. 500 and 1,700 m, and can conveniently be subdivided as (1) Neopycnodonte-Desmophyllum framestone, (2) Desmophyllum-Caryophyllia framestone, (3) Madrepora-Lophelia rudstone, (4) Pelagic mudstone and wackestone, and (5) Siliciclastic-carbonate conglomerate and breccia. Unconsolidated skeletal sediments containing corals mainly occur on gentler topographic situations between ca. 140 and 600 m and can be subdivided as: (A) Lophelia-Madrepora rubble, (B) Dendrophyllia rubble, (C) Stenocyathus rubble, (D) Caryophyllia calveri rubble, and (E) fine-grained sediment with octocoral axes. Many of these facies types are also present in the western part of the Mediterranean and have fossil representatives from the Pleistocene to the Recent. Radiocarbon dating (AMS-14C) reveals Younger Dryas ages between 12.4 and 12.0 ka cal BP for Lophelia pertusa and Madrepora oculata. Desmophyllum dianthus occurs during the Last Glacial Maximum (21.8 ka cal BP) and the Younger Dryas (11.7 ka cal BP), as well as during the Late Holocene and subrecent ...